Designing effective solid catalysts for biomass conversion: aerobic oxidation of ethyl lactate to ethyl pyruvate. Issue 8 (29th March 2018) - Zhang, Wei; Ensing, Bernd; Rothenberg, Gadi; Raveendran Shiju, N.
Abstract : A novel highly efficient solid catalyst in which vanadia is supported on pyridine-rich carbon is designed for the oxidation of ethyl lactate to ethyl pyruvate. Abstract : The direct oxidative dehydrogenation of lactates with molecular oxygen is a promising route for producing bio-based pyruvates. But practical implementation of this route means high yields and mild conditions, which in turn require expensive noble-metal catalysts. Here we report a novel catalytic approach for efficient conversion of ethyl lactate to ethyl pyruvate. We show that vanadia supported on activated carbon acts synergistically with homogeneous pyridine-type additives, giving high conversion and selectivity. Control experiments and simulations show that the reaction follows a two-step pathway: first, the pyridine–lactate complex forms, followed by transfer to the vanadium active site where the oxidation occurs. Building on these results, we design a new solid catalyst where the vanadia sites are impregnated on a pyridine-rich carbonaceous support made from poly(4-vinylpyridine). This catalyst, made from abundant elements, combines the advantages of the homogeneous pyridine additive and the vanadia active site. This combination lowers the local mass-transfer barriers and improves the stability. The catalyst gives over 90% selectivity at 80% conversion at 130 °C and 1 atm oxygen, and can be reused at least five times without losing activity.